An Electroencephalographic Investigation of the Filled-Duration Illusion - Mitsudo, Takako; Gagnon, Caroline; Takeichi, Hiroshige; Grondin, Simon (Frontiers in Integrative Neuroscience, 2012)
The study investigated how the brain activity changed when participants were engaged in a temporal production task known as the “filled-duration illusion”. Twelve right-handed participants were asked to memorize and reproduce duration of time intervals (600 or 800 ms) bounded by two flashes. Random trials contained auditory stimuli in the form of three 20-ms sounds between the flashes. In one session, the participants were asked to ignore the presence of the sounds, and in the other, they were instructed to pay attention to sounds. The behavioral results showed that duration reproduction was clearly affected by the presence of the sounds and the duration of time intervals. The filled-duration illusion occurred when there were sounds; the participants overestimated the interval in the 600-ms interval condition with sounds. On the other hand, the participants underestimated the 800-ms interval condition without sounds. During the presentation of the interval to be encoded, the contingent negative variation (CNV) appeared around the prefrontal scalp site, and P300 appeared around the parieto-central scalp site. The CNV grew larger when the intervals contained the sounds, whereas the P300 grew larger when the intervals were 800 ms and did not contain the sounds. During the reproduction of the interval to be presented, the Bereitschaftspotential (BP) appeared over the fronto-central scalp site from 1000 ms before the participants' response. The BP could refer to the decision making process associated with the duration reproduction. The occurrence of three ERP signatures, the P300, CNV, and BP, suggests that the fronto-parietal area, together with supplementary motor area (SMA), is associated with timing and time perception, and is modulated by the filled-duration illusion.